“Teaching Competency Of Secondary School Teachers In Relation To Their Teaching Aptitude.” - Jai Krishan; Dr. Rosy S. Fernandes (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Teaching is a noble and challenging profession, and teachers with sound professional teaching attitudes can fulfil the heavy responsibilities of nation-building as they are adequately prepared for their tasks. The teachers who help their students in all possible ways and are fully dedicated to their profession have a good attitude towards teaching. They should have an interest in this noble profession and have a favorable attitude towards teaching. The present study attempts to investigate the teaching competency of secondary school teachers in relation to their teaching aptitude. Utilizing a quantitative, descriptive survey design, 200 secondary school teachers from Yamuna Nagar, Haryana, were randomly selected. Data were gathered using the "Teaching Competency Assessment Battery" by Dr. Jasmine Kamala Sunira J. (2012) and a Teaching Aptitude Scale, with statistical analysis involving mean, standard deviation, t-test, and correlation. The findings reveal urban teachers exhibit higher competency than rural teachers, and government school teachers outperform private school teachers. Additionally, a significant positive correlation (r = 0.73) was found between teaching competency and teaching aptitude, indicating that greater teaching aptitude is associated with higher teaching competency. The study highlights the need for targeted interventions to improve rural teachers' competency by addressing resource and training disparities, emphasizing continuous professional development to enhance teaching effectiveness, and recommending further research and efforts in teacher training to improve teaching aptitude and competency.